Latest Innovations in Facilities and Infrastructure Management: Implementation of an Efficient Management System - Rina, Lelahester; Sitorus, Destri Sambara; Santoso, Tri Nugroho Budi (Kelola: Jurnal Manajemen Pendidikan, 2024)
Schools face significant challenges in managing facilities and infrastructure due to limited awareness of security risks, maintenance procedures, and damage prevention strategies. This research addresses this gap by developing a facilities and infrastructure management system using the ADDIE model. This system not only aims to improve the efficiency and effectiveness of school asset management but also serves as a practical learning tool for vocational high school students specializing in office management and business services. This research employed a Research and Development (R&D) approach. The data conducted by using questionnaire and analyzed descriptively. The developed facilities and infrastructure management system underwent evaluation, and the findings confirmed its highly recommended and effectiveness in streamlining school asset management. Additionally, the system proved to be a suitable educational tool for vocational students, enhancing their practical skills and knowledge.